PERANAN LINGKUNGAN KELUARGA (ORANG TUA) TERHADAP PERKEMBANGAN KEPRIBADIAN ANAK - Hadi, Irawan (Musawa: Journal for Gender Studies, 2021)
Family is the first environment recognized by children. Children spend most of their time with family. In family environment, parents have important roles in shaping children’s personality because their habits can be imitated by the children. In a family, everyone is influential, but the father and mother are the most influential. Educating children is the most important task for parents because it can affect the success of the family. However, the success of the family means nothing if it fails in educating and shaping children’s character and personality in accordance with the parents’ expectations. Family is the most significant institution in shaping children’s personalities. The essence of education is the responsibility of the family, while formal education is only a part of it. Parents have the greatest role to influence children when they are sensitive to external influences by educating them according to their own pace. Parents are the ones who should know best when and how their children learn.